NOVEL ANIMAL WELL BEING CENTRIC ZOO LAYOUT MODEL AND ITS APPLICATION AT DHAULADHAR NATURE PARK (A SMALL ZOOLOGICAL PARK) - Kohli , Bharat; Thakur, Vishal (International Journal of Engineering Technologies and Management Research, 2021)
Zoological parks are the ex-situ conservation facilities to complement and strengthen the national efforts in conservation and strengthen the rich biodiversity of the country, particularly the fauna.[1]The architectural design or the map of the zoo depicting location and dimensions of the office,exhibit area, indoor holding area, visitor paths etc are some of the major components of Master (Layout) Plan of the Zoo. Central Zoo Authority is the competent authority to approve the Master (Layout) Plan of the recognized zoological parks recognized by CZA. This Master (Layout) Plan model design takes into account of 3 key parameters that one should keep in mind while designing the zoo: Animal welfare (i.e., making animal housing facility as comfortable as possible), seamless visitor experience and smooth working of zoo management personnel.